Semiotic Analysis of the Meaning of the Instant Noodle Advertisement Message "Indomie Ramadan Edition" - Afrila Sholihah; Indah Rohmatillah (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2024)
The rapid development of the business world makes management in the company have to find the best way to market their products. Advertising is one of the media to promote goods or services that aim to increase sales by building a product image to consumers. Advertising is a special form of communication to fulfill marketing functions that are easily accepted by the market. Communication conveyed in advertising can be verbal or non-verbal. One of the advertisements that provides a product image is the Indomie noodle product, where there is a special segmentation applied by marketers that is issued in the month of Ramadan. Indomie's ads give rise to a message of tolerance that is conveyed implicit from the flow, setting and packaging of the product. The way of a creative approach to advertising using the language of communication by paying attention to appropriateness can instill a good image in the product. The research method used in this study is qualitative with the Charles Sanders Pierce semiotics model. With qualitative interpretation, the researcher made observations on the signs advertised by Indomie, so as to find out the content of the message and the reason for the existence of two segments in the advertisement. As a result of the analysis conducted by the researcher, there are three things seen from the advertisement, namely Representation, Object, Interpreter, where the Indomie advertisement in the Ramadan edition wants to display a message to consumers, namely tolerance between humans and on the other hand, it is expected that the audience or consumers will continue to carry out positive activities in the month of Ramadan, even if only at home. By still displaying the product at the end of the segment as a form of promotion and to build the image of the product.